Objectification and the Male Gaze: A Semiotic Analysis of Women's Representation in Tyla's Music Video Water - Haq, Rona Arinal; Yahdini, Azka Tsania (Universitas Ahmad Dahlan, 2024)
Women are often represented as objects in popular media, including music videos. This results in the subordination of women and the normalization of sexual harassment. This research focuses on examining the visuals displayed in Water Tyla's music video